STRATEGIC PLANNING FOR OPTIMIZATION OF GREEN OPEN SPACE BASED ON SUSTAINBLE DEVELOPMENT (Study on Flora Parks Surabaya) - OKTARIZKA REVIANDANI (Journal Publicuho, 2021)
Public Green Open Space is one of the important components for managing the city. The Surabaya City Cleanliness and Green Open Space Service in terms of providing public green open space, namely the Flora Park. Flora Park is one of the parks in Surabaya that has the potential to fulfill community rights arising from the presence of public spaces, this can be seen from its strategic location and diversity of facilities. In achieving the optimization of the Flora Park, the Surabaya City Government has explained in the Strategic Plan (RENSTRA) of the Surabaya City Cleanliness and Green Open Space Service for 2016-2021, namely through the Green Open Space Management Program which includes activities for the arrangement of green open spaces, maintenance, and procurement of park and trail facilities. Green, and Maintenance and Procurement of Recreational Park Facilities and Infrastructure. Therefore, researchers chose the focus of strategic planning carried out by the Surabaya City Cleanliness and Green Open Space Service.This study aims to identify, identify and analyze the strategic planning carried out by the Surabaya City Cleanliness and Green Open Space Service in optimizing the Flora Park based on sustainable development in the city of Surabaya and to analyze the driving factors and inhibiting factors of strategic planning in the optimization of the Flora Park in the city of Surabaya. The type of research used in the preparation of this research is descriptive research with a qualitative approach.The results of this study indicate that the strategic planning in optimizing the Flora Park carried out by the Surabaya City Cleanliness and Green Open Space Service has been running quite smoothly. The strategy of the Surabaya City Cleanliness and Green Open Space Service in optimizing the Public Flora Park based on sustainable development is following the 3 pillars contained in sustainable development which include social-based strategies, economic-based strategies, and environment-based strategies. The driving factor in optimizing the Flora Park in Surabaya is having institutions or organizations involved in optimizing the Flora Park in Surabaya, green open space management programs, having human resources, very high community participation, and collaboration with the private sector. While the inhibiting factor that can affect the success of the optimization of the Flora Park in Surabaya is limited funds for the implementation of activities.